Effects of annual fluctuation of environmental factors on starch properties in potato tuber development - Noda, Takahiro; Tsuda, Shogo; Mori, Motoyuki; Sisuki, Tatsuro; Takigawa, Shigenobu; Matsuura-Endo, Chie; Yamauchi, Hiroaki; Sarker, Md. Zaidul Islam (Wiley - V C H Verlag GmbH & Co. KGaA, 2011)
To test the effects of the annual fluctuation of the environmental factors on the starch properties in potato tuber development, starches were isolated from potato cultivars grown for ten consecutive years (2001–2010) on the experimental farm in Memuro, Hokkaido, the northernmost island of Japan. The median granule size, phosphorus content, and rapid visco-analyzer pasting properties, peak viscosity, breakdown, and pasting temperature of these starches were analyzed. Daily temperature and precipitation records in Memuro were obtained from the Japan Meteorological Agency. Moreover, the correlation coefficients of yearly accumulated temperature and precipitation from flowering to harvesting with all the starch quality parameters were calculated. No relationships of accumulated temperature with median granule size, peak viscosity, and breakdown were found. The low phosphorus content was slightly associated with the high accumulated temperature. The pasting temperature was significantly and positively correlated with the accumulated temperature, suggesting that the pasting temperature strongly responds to the environmental temperature during potato tuber development. In contrast, all the starch quality parameters were almost irrespective of the precipitation during potato tuber development.